Are You Aware of Your Data Privacy? The Case of Digital Contact Tracing Applications (MySejahtera) - Aji Z.M.; Mohd Salleh N.S.; Zakaria N.H.; Mohd Khalid A.H. (IEEE Computer Society, 2023)
Contact tracing; Control measures; COVID-19 pandemic; Descriptive statistics; Digital contact tracing application; Mysejahterum app; Online surveys; Privacy concerns; Social media; User awareness; Data privacy